International practice in the development of voluntary health insurance schemes and the potential for their implementation in Ukraine - Nazarenko, Iaroslava; Tesliiuk, Nataliia; Levkovets, Nataliia; Turpak, Tetiana (Актуальні питання економічних наук, 2026)
This article aims to examine international practices in the development of voluntary health insurance systems, identify their key features, advantages and disadvantages, and determine the opportunities, tools and mechanisms for applying best practices to the Ukrainian context, taking into account the specific nature of the domestic healthcare system, the level of development of the insurance market and European integration priorities The study utilised the following methods: systematic analysis to examine VHI systems as components of healthcare systems; comparative analysis to compare different VHI models; statistical analysis to process data on VHI markets in different countries; and the generalisation method to formulate conclusions and recommendations regarding the adaptation of international experience. Results. The main models of voluntary health insurance used in the healthcare systems of various countries have been systematised. Their key approaches to organization and operations have been analysed. The strengths and weaknesses of the analysed VHI models have been examined. Priority strategic directions for integrating voluntary health insurance into the domestic healthcare system have been outlined. Conclusions. The study has shown that voluntary health insurance (VHI) in developed countries serves as a flexible complement to state or compulsory healthcare financing schemes, expanding the range of services, accelerating access to treatment, and improving its quality. The results of the analysis confirm that, to implement international experience in Ukraine, it is necessary to take into account institutional, economic, and social realities, establish cooperation between insurers and clinics, improve the regulatory framework, and increase public confidence, which will ensure wider access to high-quality medical care and reduce the burden on the budget.